The Efficacy and Safety of Preoperative Lumbar Drain Placement in Anterior Skull Base Surgery - Ackerman, Paul D.; Spencer, Drew A.; Prabhu, Vikram C. (Journal of Neurological Surgery Reports, 2013)
This study assesses the efficacy of preoperative lumbar drain (LD) placement prior to elective open cranial and endoscopic anterior skull base (ASB) surgery in reducing postoperative cerebrospinal fluid (CSF) leak. A retrospective review of 93 patients who underwent LD placement at our institution between 2006 and 2011 was performed. Of these patients, 43 underwent elective LD placement prior to ASB surgery; 2 patients had evidence of CSF rhinorrhea prior to surgery, and 41 had no evidence of a preoperative CSF leak. Of those 41 patients, 2 developed CSF rhinorrhea (2/41= 4.9%) as a result of surgery—all in our endoscopic patient population (N = 21; 2/21= 9.5%). No postoperative CSF leaks were noted in our open ASB surgery cohort (N = 20). Other complications were rare, but we encountered two instances of delayed malignant cerebral edema in the open ASB cohort that are discussed in detail. Overall, preoperative LD placement was found to be an effective means of preventing postoperative CSF leaks after ASB approaches, but potential and significant intracranial complications may occur in select patients that merit careful consideration prior to LD placement.
Keywords: cerebrospinal fluid; lumbar drain; craniotomy; anterior skull base; endoscopic